Research methodology in strategy and management. Vol. 1 - Ketchen, David J.; Bergh, Donald D. (Research methodology in strategy and management., 2004)
Research methods present the strategic management field with great opportunities and challenges. This first volume includes three types of chapters aimed at exploiting the opportunities and meeting the challenges. One group of chapters addresses broad issues of science, including the state of strategy research, issues surrounding the age of data, and how to build cumulative knowledge within the strategic management field. A second group of chapters highlight ways to improve specific practices, including the measurement of knowledge, the assessment of limited dependent variables, and designing studies. A final group of chapters describe how strategy researchers can better use particular methods. These methods include social network analysis, longitudinal analysis, qualitative methods, survey research, and structural equation modeling. Collectively, the chapters offer state of the art thinking about research methodology provided by intellectual leaders within the strategic management field.